Molecular surveillance of Cryptosporidium spp., Giardia duodenalis, and Enterocytozoon bieneusi by genotyping and subtyping parasites in wastewater. - Na Li; Lihua Xiao; Lin Wang; Shuming Zhao; Xukun Zhao; Liping Duan; Meijin Guo; Lili Liu; Yaoyu Feng (Public Library of Science (PLoS), 2012)
BACKGROUND: Despite their wide occurrence, cryptosporidiosis and giardiasis are considered neglected diseases by the World Health Organization. The epidemiology of these diseases and microsporidiosis in humans in developing countries is poorly understood. The high concentration of pathogens in raw sewage makes the characterization of the transmission of these pathogens simple through the genotype and subtype analysis of a small number of samples. METHODOLOGY/PRINCIPAL FINDINGS: The distribution of genotypes and subtypes of Cryptosporidium spp., Giardia duodenalis, and Enterocytozoon bieneusi in 386 samples of combined sewer systems from Shanghai, Nanjing and Wuhan and the sewer system in Qingdao in China was determined using PCR-sequencing tools. Eimeria spp. were also genotyped to assess the contribution of domestic animals to Cryptosporidium spp., G. duodenalis, and E. bieneusi in wastewater. The high occurrence of Cryptosporidium spp. (56.2%), G. duodenalis (82.6%), E. bieneusi (87.6%), and Eimeria/Cyclospora (80.3%) made the source attribution possible. As expected, several human-pathogenic species/genotypes, including Cryptosporidium hominis, Cryptosporidium meleagridis, G. duodenalis sub-assemblage A-II, and E. bieneusi genotype D, were the dominant parasites in wastewater. In addition to humans, the common presence of Cryptosporidium spp. and Eimeria spp. from rodents indicated that rodents might have contributed to the occurrence of E. bieneusi genotype D in samples. Likewise, the finding of Eimeria spp. and Cryptosporidium baileyi from birds indicated that C. meleagridis might be of both human and bird origins. CONCLUSIONS/SIGNIFICANCE: The distribution of Cryptosporidium species, G. duodenalis genotypes and subtypes, and E. bieneusi genotypes in urban wastewater indicates that anthroponotic transmission appeared to be important in epidemiology of cryptosporidiosis, giardiasis, and microsporidiosis in the study areas. The finding of different distributions of subtypes between Shanghai and Wuhan was indicative of possible differences in the source of C. hominis among different areas in China.